PENGARUH KEPEMILIKAN MANAJERIAL DAN AUDIT FIRM SIZE TERHADAP FEE AUDIT (Studi Empiris pada Perusahaan Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Galih Alfian Pratama; Herry Laksito (Diponegoro Journal of Accounting, 2022)
The aims of this study to analyze and test the effects of managerial ownership and audit firm size on audit fees in financial companies listed in Indonesian Stock Exchage. The companies used as the population in this study are financial companies listed on the Indonesian Stock Exchange in 2018-2020. Audit fee in this study is the dependent variable and for independent variable using managerial ownership and audit firm size. This study also uses control variables such as firm size, leverage, current, loss, and growth.Based on the purposive sampling method, the number of financial companies used as a sample is 54 companies. This study using multiple linear regression method to analyze the research data. The results of this study indicate that managerial ownership has no significant relationship with audit fees in Indonesian financial companies. Meanwhile, audit firm size has a significant relationship with audit fees in Indonesian financial companies.